Selective mPGES-1 Inhibitor Ameliorated Adjuvant-Induced Arthritis in the Rat Model - Min Ji Kim; Hwi-Ho Lee; Choi Kim; Ja Yeon Lee; Kyung-Sook Chung; Kyung-Tae Lee; Jae Yeol Lee (Journal of Chemistry)
Endogenous prostaglandin E2 (PGE2) plays an important role in maintaining the homeostasis conditions. However, the overexpression of PGE2 in response to various inflammatory stimulations is an important target of anti-inflammatory drugs. Both inducible COX-2 (cyclooxygenase-2) and mPGES-1 (microsomal prostaglandin E2 synthase-1) enzymes are responsible for the inflammatory overexpressed PGE2 production. Among them, mPGES-1 is regarded as a more promising ideal target for anti-inflammatory drugs without the gastrointestinal and cardiovascular side effects. As our continuous research for the discovery of novel mPGES-1 inhibitors, we have characterized MPO-0144 as a selective mPGES-1 inhibitor with a selectivity index of >270 over COX-1 and >25 over COX-2, respectively. Herein, we evaluated the anti-inflammatory effect of MPO-0144 in an adjuvant-induced arthritis rat model. MPO-0144 attenuated the inflammatory responses without severe gastrointestinal side effects and organ toxicities. These overall data suggest a possibility that MPO-0144 downregulates PGE2 production by potent mPGES-1 and weak COX-2 inhibitory activities, thus attenuating the paw swelling in AIA (adjuvant-induced arthritis) rat models. MPO-0144 also exhibited favorable ADMET profiles. However, MPO-0144 did not show any inhibitory effects on human mPGES-1 enzyme at a high concentration. Therefore, MPO-0144 represents a valuable pharmacological tool for the study of regulation of inducible mPGES-1 in an inflammatory arthritis rat model.